Risk of Gynecological and Breast Cancers in Workers Exposed to Diesel Exhaust: A Systematic Review and Meta-Analysis Of Cohort Studies - D'Agostini, Marika; Collatuzzo, Giulia; Teglia, Federica; Boffetta, Paolo (La Medicina del Lavoro, 2024)
Background: This study aimed to explore the association between occupational exposure to diesel exhaust (DE) and gynaecological and breast cancers. Methods: A systematic review was performed to identify cohort studies reporting results on the association between occupational exposure to DE and risk of gynaecological and breast cancers. STROBE guidelines and PECOS criteria were followed. We identified 6 studies for breast cancer (BC), 4 for cervical cancer (CC), 4 for endometrial cancer (EC) and 7 for ovarian cancer (OC). Random-effects meta-analyses were conducted on the relationship between DE exposure and BC, CC, EC, and OC risk; 95% confidence intervals (CI) and prediction intervals (PI) were reported. We investigated between-study heterogeneity and potential publication bias using Egger's test. Results: No associations were observed between occupational DE exposure and risk of BC [RR=0.93; CI: 0.77-1.13; PI:0.50-1.73, I2=80.31%], EC [RR=0.89; CI: 0.75-1.05; PI:0.61-1.30, I2=0.78%], and OC [RR=1.08; CI: 0.89-1.32, PI: 0.76-1.56, I2=11.87%]. A weak association was observed for CC [RR=1.41; CI: 1.17-1.17; PI:0.85-2.30, I2=6.44%]. No between-study heterogeneity or publication bias was detected. Conclusions: This study identified an association between DE exposure and CC, which was not adjusted for potential confounders. No evidence of an association was found with BC, EC, and OC.